Missionary Diplomacy Religion and Nineteenth-Century American Foreign Relations - Conroy-Krutz, Emily (Ithaca Cornell University Press, 2024)
No detailed description available for "Missionary Diplomacy".
"Missionary Diplomacy traces the connections between the Protestant foreign mission movement and the US State Department over the nineteenth century, with particular attention paid to the development of new ideas about citizenship, religious freedom, and humanitarianism."--
Description based on publisher supplied metadata and other sources
Keywords: Christianity and international relations -- United States -- History -- 19th century; Missionaries -- Political activity -- History -- 19th century; Protestantism -- Influence; United States -- Foreign relations